The Relations of Particles - B. Okun Lev (World Scientific Pub Co Inc, 1991)
A collection of review talks and popular science papers by Lev Okun. The talks were given at major international conferences on elementary particle physics during the 1980s. The papers discuss experimental tests of fundamental physical principles and the concept of mass in relativity theory.